Histamine in cancer immunology and immunotherapy. Current status and new perspectives - María de la Paz Sarasola; Mónica A. Táquez Delgado; Melisa B. Nicoud; Vanina A. Medina (Wiley, 2021)
Abstract Cancer is the second leading cause of death globally and its incidence and mortality are rapidly increasing worldwide. The dynamic interaction of immune cells and tumor cells determines the clinical outcome of cancer. Immunotherapy comes to the forefront of cancer treatments, resulting in impressive and durable responses but only in a fraction of patients. Thus, understanding the characteristics and profiles of immune cells in the tumor microenvironment (TME) is a necessary step to move forward in the design of new immunomodulatory strategies that can boost the immune system to fight cancer. Histamine produces a complex and fine‐tuned regulation of the phenotype and functions of the different immune cells, participating in multiple regulatory responses of the innate and adaptive immunity. Considering the important actions of histamine‐producing immune cells in the TME, in this review we first address the most important immunomodulatory roles of histamine and histamine receptors in the context of cancer development and progression. In addition, this review highlights the current progress and foundational developments in the field of cancer immunotherapy in combination with histamine and pharmacological compounds targeting histamine receptors.